Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Christine Watkins, Howard Watkins holding Adam Watkins, Albert Watkins, Jane Fonda, Rose Watkins in family living room